Trajetórias sertanejas: agenciamento, conflito e migração no Rio Grande do Norte (1877 a 1904) - Maciel, Francisco Ramon de Matos (2020)
This paper aims to analyze through the writings of social history how people from Rio Grande do Norte, Ceará, Paraíba and Pernambuco alike, shared their experiences on the migration, organization and resolution of conflicts during the drought of 1877 until 1904. More than that our perspective was to understand the development of a regional popular politics which grew on the everyday supply crisis and work relations, aside from the readaptation strategies adopted by the migrants on the several places reached by the migration. This popular politics is settled on a group of customs, rules and values, which belong to a set of actions that the subordinates have developed in their relations with the agents of power, their culture and moments of conflict. Therefore, the migrants organization happened trough the family institution, the feminine role, the collective actions and the (in)direct conflict with the political powers. The agencying occurred wherever the sertaneijo’s spreading reached, outlining some of its experiences on city spaces, agricultural colonies and immigration inns. Some of the sources used on this research were periodicals, reports of public aid commission and agricultural colonies, imigrational inn's checklists, letters and speeches of the presidents of the province, documents of public prosecutors and justice officials, pictures and memory books. Therefore, understanding this formation as a social phenomenon of the time is to be attentive to the trajectory of resilience and resistance of the migrants from Rio Grande do Norte in Brazilian society in the end of the 19th century.